Illegal trading in the cross-border of Indonesia and Enclave Oecusse, Timor Leste - Aplonia Pala; Moh. Zamili (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Cross-border trade wrapped in kinship is the hallmark of residents of the borders of Indonesia and Timor Leste. This study aims to analyze the cross-border trade activities of district Timor Tengah Utara Republic of Indonesia and District Enclave Oecusse, Republik Demokrasi Timor Leste. Research on illegal trade was carried out from January 2019 to December 2021. Throughout the study, the authorities were aware of the illegal trade but there was omission because the profits earned were greater than the legal transactions. The types of illegal trade include: subsidized fuel household furniture clothing, cigarettes, and groceries. A qualitative approach is used to explore the context of the border area and the main phenomena. Opinions, perceptions, and feelings of participants regarding the activities of trade area known as the mouse paths (Jalan Tikus) were obtained through field work and indepth interviews. The results of this study indicate several factors, from an economic perspective, such that it provides many benefits because the currency transactions used are US; security supervision at the border is not yet tight and maximal; geographical conditions close to residential areas make it easier to smuggle goods into Timor Leste. This study concludes that there is a need to improve supervision of exit gates, entry of people and goods passing through the border entrance and the management of cross-border markets that have been built in support of bilateral cooperation.